2012
DOI: 10.1128/jb.06576-11
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Phenotypes Mediated by Aminoacyl-Phosphatidylglycerol Synthases

Abstract: The specific aminoacylation of the phospholipid phosphatidylglycerol (PG) with alanine or with lysine catalyzed by aminoacylphosphatidylglycerol synthases (aaPGS) was shown to render various organisms less susceptible to antibacterial agents. This study makes use of Pseudomonas aeruginosa chimeric mutant strains producing lysyl-phosphatidylglycerol (L-PG) instead of the naturally occurring alanyl-phosphatidylglycerol (A-PG) to study the resulting impact on bacterial resistance. Consequences of such artificial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 92 publications
2
42
0
Order By: Relevance
“…38 Several studies have tried to determine the phenotypical changes correlated with synthesis of Lys-PG compared with Ala-PG in S. aureus and P. aeruginosa . 24,30 These investigations showed that substitution of Lys-PG (which confers a net charge of +1) with Ala-PG (which bears a neutral net charge) did not affect bacterial susceptibility to CAMPs such as nisin and gallidermin, or to the CAMP-like antibiotic daptomycin. These findings suggest that the α amino group of the aa moiety of aa-PG alone is able to enhance antimicrobial resistance in bacteria.…”
Section: Aapgs Mediated Lipid Remodeling Uses Several Aa-trnas As Submentioning
confidence: 99%
See 2 more Smart Citations
“…38 Several studies have tried to determine the phenotypical changes correlated with synthesis of Lys-PG compared with Ala-PG in S. aureus and P. aeruginosa . 24,30 These investigations showed that substitution of Lys-PG (which confers a net charge of +1) with Ala-PG (which bears a neutral net charge) did not affect bacterial susceptibility to CAMPs such as nisin and gallidermin, or to the CAMP-like antibiotic daptomycin. These findings suggest that the α amino group of the aa moiety of aa-PG alone is able to enhance antimicrobial resistance in bacteria.…”
Section: Aapgs Mediated Lipid Remodeling Uses Several Aa-trnas As Submentioning
confidence: 99%
“…23 In more recent years, it was shown that LysPGS is only one member of a large family of aminoacyl-PG synthase (aaPGS) homologs spanning nearly all known bacterial phyla. Some homologs are also present in archaeal methanogens, 24 but no examples have been identified in eukaryotic genomes. 1 Aminoacyl-phosphatidylglycerol synthases (aaPGSs), as these enzymes are collectively called, are bifunctional enzymes.…”
Section: Trna-dependent Aminoacylation Of Membrane Phosphatidylglycerolmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, aa-PGS enzymes can be considered virulence factors and thus have been termed "multiple peptide resistance factors." In Pseudomonas aeruginosa, aminoacylation of PG also was found in response to acidic environmental conditions (2,5), inter alia. P. aeruginosa is the dominant pathogen that colonizes the lung of patients suffering from cystic fibrosis.…”
mentioning
confidence: 99%
“…1) reduce the overall net negative charge of the membrane, making it less susceptible to cationic antimicrobial peptides (CAMPs). Such CAMPs often are synthesized as innate immunity host-defense peptides in response to bacterial infections (2)(3)(4)(5). Fundamental work with the Gram-positive pathogen Staphylococcus aureus indicated aa-PGS-mediated nonsusceptibility to vancomycin (an antibiotic of last resort), resistance to host antimicrobial peptides (defensins), and protection against neutrophil killing (6)(7)(8)(9).…”
mentioning
confidence: 99%